Analysis Of Consumer Knowledge In Adopting Tiens Brand Health Supplement Products In Banda Aceh City - Ismail; Nasir (Indonesian Journal Economic Review (IJER), 2024)
The research aims to analyze Tiens product users, especially in consuming the company's new products, so that with product knowledge consumers are interested in adopting these new products. Which creates a consumption situation that is in line with market demand in penetrating the existing market share. Data collection was carried out using purposive sampling by distributing questionnaires to 90 respondents. The data obtained was then processed through the SPSS (Statistical Package for Social Science) program using descriptive statistical analysis equipment in the form of average values ​​and percentages with the same frequency. The research results show that the consumption situation has a direct influence on consumers in adopting the company's new product, namely Shredded Tuna Fish which is quite popular and is only produced by Tiens to be marketed to the entire Muslim community in the city of Banda Aceh. Based on the results of the discussion, it shows that the majority of respondents were <20 to 30 years old, 44 respondents or 48.9% were unmarried, most of whom were women or women who had a high school to university level education with a middle to upper income level. . To maintain consumer loyalty, the company must continue to maintain the quality of the product content without reducing the content or content of the ingredients, replacing or recycling them so that it affects the quality and quality of the product. In terms of service, it needs to be improved considering the tight competition in the Multi Level Marketing (MLM) field at this time.